ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2013 – 2017 - Restu Ayu Puspita, 16.05.62.0010; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study examines the Effect of Capital Structure, Company Size, Liquidity and Profitability on Firm Value. This research was conducted at the Indonesia Stock Exchange using the food and beverage sector company. The population in this study were all food and beverage sector companies listed on the Indonesia Stock Exchange in 2013 until 2017. The samples used in this study were all food and beverage sector companies The results of this study indicate that the capital structure (DAR) has no effect (positive is not significant), Company size does not affect (positive not significant) Liquidity) no effect (negative not significant), profitability has a significant positive effect on firm value.